2012
DOI: 10.1136/bmjopen-2011-000496
|View full text |Cite
|
Sign up to set email alerts
|

Improving the recruitment activity of clinicians in randomised controlled trials: a systematic review

Abstract: Background: Poor recruitment to randomised controlled trials (RCTs) is a widespread problem. Provision of interventions aimed at supporting or incentivising clinicians may improve recruitment to RCTs.Objectives: To quantify the effects of strategies aimed at improving the recruitment activity of clinicians in RCTs, complemented with a synthesis of qualitative evidence related to clinicians' attitudes towards recruiting to RCTs. Study eligibility criteria: Quantitative studies were included if they evaluated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
399
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(418 citation statements)
references
References 45 publications
(69 reference statements)
17
399
0
3
Order By: Relevance
“…Recruitment difficulties were often attributed to logistical issues (such as a lack of time for research activities) or patient-related factors (including strong treatment preferences or disliking randomisation). In 2012, Fletcher and colleagues [18] highlighted the potential of using qualitative research to understand recruitment, and since this, qualitative studies have shed further light on the challenges of recruiting patients [24,[26][27][28][29][31][32][33][34][36][37][38]40,43,45,48,49,[52][53][54]. Taken together, these highlight how recruitment is a complex and fragile process in which recruiters can experience emotional and …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recruitment difficulties were often attributed to logistical issues (such as a lack of time for research activities) or patient-related factors (including strong treatment preferences or disliking randomisation). In 2012, Fletcher and colleagues [18] highlighted the potential of using qualitative research to understand recruitment, and since this, qualitative studies have shed further light on the challenges of recruiting patients [24,[26][27][28][29][31][32][33][34][36][37][38]40,43,45,48,49,[52][53][54]. Taken together, these highlight how recruitment is a complex and fragile process in which recruiters can experience emotional and …”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that information conveyed during recruitment appointments varies considerably in content and quality [13], and patients often have a poor understanding of RCT concepts [14][15][16][17]. A systematic review of interventions to improve the recruitment activity of clinicians reported that the most promising interventions were studies that used qualitative research to identify key issues and develop interventions to improve recruitment [18]. This focused review provides an introduction to qualitative research techniques and summarises how this approach can be used to understandand subsequently improve-recruitment to RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…There A number of reviews have been undertaken on the topic of recruitment to RCTs. 3,19,20 The evidence base drawn on by these reviews primarily originates from secondary care and are medical in nature. Whilst there is a suggestion that some intervention may be effective in improving recruitment (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The concept that T2DM is permanent is reflected in earlier literature [25][26][27][28] As currently advocated [14], our study questionnaire was grounded in rigorous qualitative work. Our practice sampling was diverse in terms of geography and underlying socioeconomic which will enhance generalizability of our findings.…”
Section: Resultsmentioning
confidence: 99%
“…Patient recruitment is a key issue affecting the conduct of RCTs [14][15][16] Little work on this group has been undertaken in the UK, where the expense of funding treatment costs makes RCTs of bariatric surgery problematic. Evidence on acceptability and willingness to participate in UK bariatric surgery trials in this group is needed to indicate feasibility and support decision making amongst researchers and funders.…”
Section: Introduction/purposementioning
confidence: 99%